Supporting the Implementation of Evidence-Based Practices for Children with ASD (Kairaranga, 2020)
The primary objective of this small-scale study was to identify ways in which Resource Teachers: Learning and Behaviour (RTLB) can work with teachers to implement evidence-based practices for children with Autism Spectrum Disorder (ASD) within aninclusive educational system. With the increasing prevalence of children with ASD in mainstream classrooms, there is a critical need to support teachers with evidence-based practices (EBPs) to improve outcomes for all students. In this study, twenty four RTLB were surveyed about professional learning and development (PLD) related to their work with teachers to implement EBPs for children with ASD. Qualitative and quantitative methods of data gathering were employed in the form of an anonymous online self-administered questionnaire. The findings revealed that, overall, this group of RTLB has a preference for PLD in the form of ongoing coaching and support with the implementation of evidence-based practices tailored to the needs of their caseload students.